Pengelolaan Aset Wisata Telaga Soda dalam Peningkatan PADes di Desa Tanggungprigel Kecamatan Glagah Kabupaten Lamongan - Mudhiatul Lailiyah; Deasy Arieffiani (Public Administration Dept, Faculty of Social and Political Science, 2023)
Soda Lake Tourism is one of the village assets managed as a tourist spot made by Pokdarwis Kreasi Telaga Soda which was previously an ordinary pond. The purpose of this study is to describe and analyze the management of tourism assets in increasing the village's original income in Telaga Soda Tourism as well as the supporting factors and inhibiting factors in the management of Telaga Soda tourism. The method used is descriptive qualitative with the sources of information being the Head of the Tangungprigel Village, the Chairperson of the Pokdarwis of the Responsibility of Prigel Village, and visitors. Data collection technique using purposive sampling. This study uses indicators from Permendagri Number 1 of 2016 concerning Village Asset Management. the results of the study indicate that the implementation of village asset management in Telaga Soda tourism in the Responsibility Prigel Village has been running in accordance with Permendagri Number 1 of 2016 concerning Village Asset Management is the implementation of Utilization, Maintenance, Administration, Reporting and supervision. Indicators that have not gone well are the implementation of Planning, Guidance and Security. The suggestions are efforts to increase the competence of tourism managers through outreach, technical guidance, training education with competent speakers, collaborating with third parties for development in the management of Telaga Soda tourism. In developing Telaga Soda Tourism, the village government and Pokdarwis must be more open in seeing opportunities and changes in the tourism sector. In addition, tourism facilities and infrastructure such as accessibility, amenities and accommodation must always be improved and improved.